2002
DOI: 10.1097/00008506-200207000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurement of Cerebral Blood Flow in Adults Using Near-Infrared Spectroscopy and Indocyanine Green: A Pilot Study

Abstract: This pilot study was designed to determine the feasibility of measuring cerebral blood flow noninvasively after an intravenous bolus of indocyanine green using near-infrared spectroscopy and pulse dye-densitometry. Feasibility aside, this study did not attempt to validate the measured values of cerebral blood flow against an established method of measurement. Twelve healthy volunteers were investigated after peripheral intravenous injection of indocyanine green. Arterial and cerebral changes in indocyanine gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 26 publications
3
56
0
Order By: Relevance
“…It has been shown that over 50% of the illuminated tissue volume in adults can be comprised of extra-cerebral tissue (Steinbrink et al, 2001). This signal contamination has been shown to cause a significant underestimation of CBF, and presumably the same would apply to CMRO 2 (Gora et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…It has been shown that over 50% of the illuminated tissue volume in adults can be comprised of extra-cerebral tissue (Steinbrink et al, 2001). This signal contamination has been shown to cause a significant underestimation of CBF, and presumably the same would apply to CMRO 2 (Gora et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…ICG can act as a Fick tracer, similar to that of an inert gas. The rate of arrival of ICG in the brain, a few seconds after the rapid injection of ICG, can be observed by NIRS (Gora et al, 2002). ICG is introduced rapidly and its rate of accumulation is measured over time.…”
Section: Cbfmentioning
confidence: 99%
“…Blood flow can be measured as a ratio of ICG accumulated to the quantity of ICG introduced over a given time (Perrey, 2008). The accumulation of ICG in the brain will be dependent on both arterial inflow and venous outflow (Gora et al, 2002). The method of measuring CBF relies on several assumptions: first, blood flow must be constant for the period of measurement.…”
Section: Cbfmentioning
confidence: 99%
See 1 more Smart Citation
“…For CBF measurements, the measured ICG tissue concentration curve is comprised of both cerebral and non-cerebral components that are highly correlated. Using tracer kinetic models to recover CBF from a contaminated curve would result in an underestimation of CBF Gora et al, 2002;Owen-Reece et al, 1996). Solutions to overcoming this challenge have been proposed, including more advanced instrumentation as well as analytical approaches, with the main goal of increasing sensitivity to cerebral components.…”
Section: Extra-cerebral Signal Contaminationmentioning
confidence: 99%